Motivation to Higher Education and its Structure - Krushelnitskaya O.I.; Polevaya M.V.; Tretiyakova A.N., (Психолого-педагогические исследования, 2019)
Features of motivation for obtaining higher education, leading motives, motivational structure are investigated. The relevance of the research is determined by the influence of the motivation peculiarities on the success in studies educational activities and subsequent work. The students of the first courses of full-time education of 12 universities of different regions of Russia took part in the research. N = 559. The analysis of such indicators of central tendency as median, mode and arithmetic mean was used to assess the relative importance of motives. Correlation analysis and cluster analysis were used to identify the structure of motivation for obtaining higher education. Motivation for obtaining higher education was defined as a distant, external to the training activity, an anticipatory motivation. The motives for ensuring material well-being in the future, professionalization, self-realization are the most significant. The structure of motivation includes two clusters of motives that are grouped around the motives of material well-being and self-realization, and a separate motive of professionalization. The motives of the first cluster can be marked as motives for socialization. Motives of the second cluster can be marked as motivation for individuation.